Solid waste management and participation of rural household members in waste-related tasks - Gabriel, Florenda Sotto (2004)
To understand solid waste management at the micro-level, a study was conducted among rural households to describe how they manage their solid waste. The study sought to describe the characteristics of household waste, waste-related practices, and participation of household members in waste-related tasks. It also explored the perception of waste-related practices of rural households and the factors that influence household waste management. Ninety households in two rural villages in Alaminos, Laguna participated in the survey conducted using questionnaires and interview schedules. The primary waste managers of the households (mostly mothers) served as the respondents of the study. Actual waste samples were collected for waste characterization. The respondents viewed as "waste" not only materials that were useless but also those considered dirty, unwanted, can cause harm to one's health and that clutter the house and its surroundings. Households generated 1.26 kg of solid waste per day with a per capita generation rate of 0.24 kg/day, composed largely of food yard waste. More than 70 percent of households carried out waste reduction and segregation. The households used a variety of disposal methods, but burning of mixed waste as common. These practices were based on the demand posed by what they identified and defined as "waste", the kinds of waste they generated and their waste management goal. The respondents' conception of waste was multi-faceted and expansive, reflecting varying dimensions of respondents concerns. The rural households practiced solid waste management in a purposeful, practical and systematic way but waste disposal practices were guided by traditional beliefs about the benefits of burning. Gender and age had some influence on the performance of waste-related tasks. Household waste-related tasks were still largely the responsibility of mothers, although fathers, daughters, sons and other household members also participated in atleast one of nine waste-related tasks. There was a difference between the actual participation and perceived ideal responsibilities of household members in terms of decision-making pertaining to household waste management. Nonetheless, the respondents appeared to be generally satisfied with how they managed solid waste in their households.